Preliminary development of a model for insects information system/ J. Roslan, M. Muzamil and S. Ana Salwa - Roslan, J.; Muzamil, M.; S., Ana Salwa (2002)
This paper discussed the development of a model for insect information system. The information system is developed using the Microsoft Access 2000 as the database and Microsoft Visual Basic 6.0 for the interface. The database was developed using Relational Database Management System (RDBMS) model. The database comprises 3 major fields which are collection specimen, specimen and species. There are 14 attributes for collection specimen namely country, island, state, district, locality, longitude, latitude, date, altitude. habitat, sex, collector/s, source locality, specimen identification; 17 attributes for specime'1 namely specimen identification, cabinet number, species identification, repository, collection event, identified by, literature cited, modification date, sound, image, DNA fingerprint, host, host plant, parasitoid, pest, pesticide and vector; and 10 attributes for species namely species identification, class, order, family, subfamily, tribe, genus, species, subspecies and authority. The system capable runs several functions such as inventory, search, loan, report and user's information record. This system will facilitate the researchers to access and retrieving insect diversity information in Malaysia. This system will be upgraded for Internet and online processing and become Malaysian Insects Online (MIOL).